2002
DOI: 10.1079/ajaa200207
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the adoption of organic farming by cash-crop producers in Austria

Abstract: Most of Austria's organic farms are located in mountainous areas und produce minly milk und beef; whereas a low percentage of cash-crop fanns are organic. As a result, the demnd for organically grown crops cannot be fully met by domestic production. This paper investigates the barriers to adoption of organic agriculture by cash-crop farmers in Austria. In a written survey, 383 conventional farmers provided information on their perception of organic farming und rated the importance of potential barriers to adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 0 publications
3
64
0
2
Order By: Relevance
“…Organic farmers thought the information was insufficient, and the associations lacked the ability to keep them informed with up-to-date standards and regulations. Another study addressed the subjective norms that motivated Austrian cash-crop producers' decisions to move toward organic practices (Schneeberger et al, 2002). Respondents were more concerned with resistance to organic farming within their families, more so than with friends.…”
Section: Introduction Factors Influencing Adoption Of Organic Farmingmentioning
confidence: 99%
“…Organic farmers thought the information was insufficient, and the associations lacked the ability to keep them informed with up-to-date standards and regulations. Another study addressed the subjective norms that motivated Austrian cash-crop producers' decisions to move toward organic practices (Schneeberger et al, 2002). Respondents were more concerned with resistance to organic farming within their families, more so than with friends.…”
Section: Introduction Factors Influencing Adoption Of Organic Farmingmentioning
confidence: 99%
“…Organic farming offers a more sustainable alternative to conventional agricultural production (see Mäder et al, 2002) and has experienced considerable growth since the 1980s in many regions of the world. In the European Union (EU), almost 4% of all utilized agricultural area was cultivated organically by 2003(see European Commission, 2005 and several European countries like Switzerland, Lichtenstein or Austria had even reached a share of about 10% (see Schneeberger et al, 2002;Willer and Yussefi, 2005). The growth of organic production has had numerous positive consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Research Fowler, & Lampkin, 2001;Schneeberger, Darnhofer, & Eder, 2002). Other studies have revealed farmers' preference of communication channels when wanting information about organic and nonorganic farming practices (Duram, 1999;Egri, 1999).…”
Section: Rq7mentioning
confidence: 99%
“…The researchers developed a 29-item questionnaire that was adapted from previous studies (Egri, 1999;Fairweather, Campbell, Tomlinson, & Cook, 2001;Midmore et al, 2001;Niemeyer & Lombard, 2003;Schneeberger et al, 2002). Seven subjective norm items were directly measured on a 7-point Likert scale ranging from strongly disagree (1) to strongly agree (7).…”
Section: Rq7mentioning
confidence: 99%